A single case report of STN-DBS for severe crack-cocaine dependence: double-blind ON vs. SHAM randomized controlled assessment - Vorspan, Florence; Domenech, Philippe; Grabli, David; Yelnik, Jérôme; Delavest, Marine; Dauré, Charles; Bellivier, Frank; Pelissolo, Antoine; Belaid, Hayat; Baunez, Christelle; Karachi, Carine; Mallet, Luc (Frontiers in Psychiatry, 2023)
Crack-cocaine dependence is a severe condition with a high mortality rate. We present here the first deep brain stimulation (DBS) trial targeting the sub-thalamic nucleus (STN) for crack-cocaine dependence. Our aim was to assess the effects of STN-DBS on cocaine craving and cocaine use, as well as STN-DBS safety and tolerance in this indication. In this pilot study, we performed double blind cross-over trials, with “ON-DBS” versus “SHAM-DBS” one-month periods. Sub-thalamic nucleus DBS failed to reduce cocaine craving and use. An episode of DBS-induced hypomania occurred after several weeks of cocaine intake at stimulation parameters previously well tolerated. Future research in cocaine dependence should either be conducted after a prolonged abstinence period or explore novel types of stimulation patterns.